Latin American Politics in the Neoliberal Era The Changing Dynamics of Class Struggle - Veltmeyer, Henry (Emerald Studies in State, Politics and Society Series, 2024)
Challenging centuries-old systems and barriers as the only study on the contemporary dynamics of the class struggle within the context of this region, this text fights back against the homogenous tides of class and capitalism to envision a richly diverse continent with more to offer than ever